Ending Parkinson's disease : a prescription for action - Dorsey, Ray; Sherer, Todd; Okun, Michael S.; Bloem, Bastiaan R. (PublicAffairs, 2021)
In this must-read guide (Lonnie Ali), four leading doctors and advocates offer a bold action plan to prevent, care for, and treat Parkinson's disease-one of the great health challenges of our time.Brain diseases are now the world's leading source of disability. The fastest growing of these is Parkinson's: the number of impacted patients has doubled to more than six million over the last twenty-five years and is projected to double again by 2040. Harmful pesticides that increase the risk of Parkinson's continue to proliferate, many people remain undiagnosed and untreated, research funding stagnates, and the most effective treatment is now a half century old.In Ending Parkinson's Disease, four top experts provide a plan to help prevent Parkinson's, improve care and treatment, and end the silence associated with this devastating disease.